Contents and Methods of al-Hadith Memorization: Perceptions of Religious Teachers in Tahfiz Schools around Kuala Lumpur and Putrajaya - Nadia Farhana Muhammad Saidi; Asyraf Isyraqi Jamil (Educan : Jurnal Pendidikan Islam, 2021)
This research attempts to gather arguments from the literature to explain the importance of memorizing al-Hadith as a complement to the curriculum of tahfiz students. The argument is further strengthened by the findings on the suitable contents and methods for students to practise from the point of view of religious teachers in tahfiz schools in Kuala Lumpur and Putrajaya. A quantitative survey was conducted to gather the opinions of 210 respondents using a questionnaire instrument. Respondents mostly agreed that al-Hadith should be memorized in the form of perfect sanad and matan. The book al-Arba’in an-Nawawiyyah has been chosen as the most ideal content among some of the proposed al-Hadith books. The tasmi’ method is considered to be the most suitable to be practised in memorizing al-Hadith. The role of nutritious food and drinks is also an added value emphasized in the things that can help students’ memorization. The findings and discussion of this study conclude that al-Hadith memorization is a thoughtful proposal in complementing the curriculum of tahfiz students. The input from this article is targeted to be a pioneer of more discussions and studies within the scope of Islamic education in our country.